2015
DOI: 10.1161/hcg.0000000000000022
|View full text |Cite
|
Sign up to set email alerts
|

Common and Rare Variants in SCN10A Modulate the Risk of Atrial Fibrillation

Abstract: Background Genome-wide association studies (GWAS) have shown that the common single nucleotide polymorphism (SNP) rs6800541 located in SCN10A, encoding the voltage-gated Nav1.8 sodium channel, is associated with PR–interval prolongation and atrial fibrillation (AF). SNP rs6800541 is in high linkage disequilibrium with the non-synonymous variant in SCN10A, rs6795970 (V1073A, r2=0.933). We therefore sought to determine whether common and rare SCN10A variants are associated with early onset AF. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
5
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 48 publications
3
55
5
4
Order By: Relevance
“…14,15 These variants are located in a locus previously linked to Brugada syndrome 24 and variations in ECG 25 in various genome-wide association studies. While rs6801957 appears to alter Na V 1.8 expression by affecting a Tbox binding element in an SCN10A enhancer region, shown decelerated time-dependent recovery from inactivation, but larger peak current and accelerated time to peak with respect to rs6795970 A Na V 1.8 (1073 Val ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 These variants are located in a locus previously linked to Brugada syndrome 24 and variations in ECG 25 in various genome-wide association studies. While rs6801957 appears to alter Na V 1.8 expression by affecting a Tbox binding element in an SCN10A enhancer region, shown decelerated time-dependent recovery from inactivation, but larger peak current and accelerated time to peak with respect to rs6795970 A Na V 1.8 (1073 Val ).…”
mentioning
confidence: 99%
“…While rs6801957 appears to alter Na V 1.8 expression by affecting a Tbox binding element in an SCN10A enhancer region, shown decelerated time-dependent recovery from inactivation, but larger peak current and accelerated time to peak with respect to rs6795970 A Na V 1.8 (1073 Val ). 15 Therefore, fine-mapping studies will be required to identify the actual causal variant, and functional studies in animal models of MS will be necessary to determine how these variants affect cerebellar dysfunction in MS. Purkinje neurons receive integrated inputs indirectly from a variety of regions in the brain and spinal cord. 26 They form the output layer of the cerebellar cortex and play a key role in cerebellar neural circuitry and function.…”
mentioning
confidence: 99%
“…showed that the G allele of rs6795970 was associated with a higher risk of AF. In addition, Jabbari et al 37. also reported that the G allele of rs6795970 increased the risk of AF.…”
Section: Discussionmentioning
confidence: 98%
“…Гомозиготный генотип GG гена SCN10A играет протективную роль в отношении развития идиопатических атриовентрикулярных блокад и блокады правой ножки пучка Гиса. [3][4][5][6][7][8]. Однако имеющиеся результаты по гену SCN10A были получены при исследовании пациентов евро-пейской, азиатской и афроамериканской популяций, среди лиц сибирской популяции данный ген ранее не изучался.…”
Section: новый генетический маркер врожденной патологии проводящей сиunclassified